Precision system for mapping terrain trafficability, tractor-implement performance and tillage quality - Azmi, Yahya; Mohd Zohadie, Bardaie; A. F., Kheiralla; S. K., Gew; B. S., Wee; E. B., Ng (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/